Images de la Révolution dans l’œuvre de Jorge González Camarena - Marie-Pierre Ramouche (Caravelle)
This article intends to analyze the representations of the Mexican Revolution in the work of the muralist painter Jorge González Camarena. Member of the second generation of Muralists, Camarena succeeded in creating a style which made the most of mural art but, at the same time, enabled him to serve the official speech which had a tendency to simplify and mystify the Revolution’s history.